Study on the propagation behavior of hydraulic fractures in deep high-stress mining panels - CHEN Liwei; WANG Dongjie; BIAN Le (河南理工大学学报. 自然科学版)
ObjectivesTo investigate the crack propagation behavior of hydraulic fracturing in deep high-stress mining panels，Methodsusing the S5207 return airway of the No. 3 coal seam in Yuwu Coal Mine as the engineering background， a hydraulic fracturing mechanical model was established to analyze the maximum circumferential tensile strain criterion and crack propagation criterion. Subsequently， a three-dimensional numerical simulation was conducted to examine the effects of the hydraulic fracturing influence factor D and in-situ stress on crack propagation. Based on field conditions， a hydraulic fracturing test plan was designed， permeability enhancement technology was implemented， and the field performance was analyzed.ResultsThe results indicate that prefabricated cracks propagate outward at an angle to the original crack and ultimately align perpendicular to the minimum principal stress direction. As the D value increases， the angle between the new and original cracks decreases， and the cracks exhibit self-similar propagation when D is sufficiently large. Under varying stress fields， crack propagation trajectories are primarily governed by the principal stress direction， ultimately aligning perpendicular to the minimum principal stress. Hydraulic fractures are vertical and exhibit stress concentration at the crack tips. On-site monitoring revealed that the observed phenomena conformed to the maximum circumferential tensile strain criterion： crack tips extended along regions of maximum circumferential tensile strain， with cracking initiated when this strain reached its peak. During fracturing， significant circumferential fractures were observed. The cracks propagated perpendicular to the minimum principal stress direction， aligning approximately with the maximum horizontal principal stress direction of the S5207 return airway， which closely matched the numerical simulation results.ConclusionsThe integration of numerical simulations， theoretical analysis， and field experiments provides valuable insights into the crack propagation behavior of hydraulic fracturing in deep high-stress mining panels. The findings offer useful references for hydraulic fracturing design and numerical simulation studies in similar mines such as Yuwu Coal Mine.